Designing E-Commerce Sales of Footwear Using the Waterfall Method - Fernando, Erick (Publisher Cv. Inara, 2023)
E-Commerce's quick growth and Indonesia's growing footwear industry offer expanding opportunities. A website-based E-Commerce Information System to promote varied Indonesian footwear brands is proposed to boost their market exposure nationally and globally. The structured Waterfall technique emphasises system development step-by-step for greater control and completion of each stage before moving on. E-Commerce software offers safe payment choices and better order management to streamline sales. It promotes using technology and data analysis to improve business and marketing decisions. This E-Commerce system's Waterfall-based strategy promises efficient online footwear sales management. Successful implementation requires careful integration and completion of developmental stages